Kinetics Adsorption Study Of Ammonia On Syrian Zeolite Ore - حبيب ليلى; علوش غياث; يونس سليمان (Latakia University Journal -Biological Sciences Series, 2022)
Zeolite may play a major role in reducing nitrogen loss during composting of agricultural residues, especially poultry manure, therefor the objective of this research was focused on the adsorption and kinetics of ammonia gas on Syrian Zeolite Ore (SZO). Adsorption of ammonia gas was studied in a close media containing increasing concentrations of ammonia gas ranging between 2.5 to16.8.mg/l NH3-N. Langmuir and Freundlich models were applied. Both models predicted the adsorption process with coefficient correlation values R2 ≥ ​​ 0.958. Kinetics adsorption was studied using pseudo first order and Intra particle diffusion models. Models constants indicated that they could predict kinetics adsorption, and models parameters indicated participation of more than one sorption mechanisms. Zeolite was moistened to levels between 5% and 45% (weight based). Increasing moisture from 5% to 25% increased absorbed amount of ammonia from 5.1 to 6.1 mg N/g SZO. Increasing hydration ratio more than 25% did not lead to additional increases in ammonia adsorption.